2015
DOI: 10.2214/ajr.14.13810
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Breakthrough Reactions in Inpatients at High Risk Receiving Premedication Before Contrast-Enhanced CT

Abstract: Patients premedicated for a previous reaction to iodinated contrast material have a breakthrough reaction rate 3-4 times the ordinary reaction rate in the general population. Patients receiving premedication for other reasons have a breakthrough reaction rate near 0%. Many patients must receive premedication to prevent one reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 17 publications
2
39
0
Order By: Relevance
“…Authors of the second randomized trial (6), which was published in 1994, showed that corticosteroid prophylaxis administered to patients in the general population (n = 1155) before the injection of modern lower-risk lowosmolality iodinated contrast material resulted in a significant reduction in aggregate and grade 1 reactions, but no significant reduction was observed in grade 2 or 3 reactions. Researchers suggested that this inability to demonstrate a reduction in clinically important moderate or severe reactions was related to study size and statistical power, but that argument raises questions about the number needed to treat (NNT) (7,8).…”
Section: Study Cohort: Population Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors of the second randomized trial (6), which was published in 1994, showed that corticosteroid prophylaxis administered to patients in the general population (n = 1155) before the injection of modern lower-risk lowosmolality iodinated contrast material resulted in a significant reduction in aggregate and grade 1 reactions, but no significant reduction was observed in grade 2 or 3 reactions. Researchers suggested that this inability to demonstrate a reduction in clinically important moderate or severe reactions was related to study size and statistical power, but that argument raises questions about the number needed to treat (NNT) (7,8).…”
Section: Study Cohort: Population Detailsmentioning
confidence: 99%
“…Although corticosteroids do prevent severe allergiclike reactions to low or iso-osmolality iodinated contrast material, the effect has been shown to be incomplete (7,14,15), breakthrough reactions can occur (14,15), and the NNT is large (7). Therefore, we are interested to know whether the costs and indirect harm associated with corticosteroid prophylaxis are greater than the potential benefits.…”
Section: Study Cohort: Population Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the efficacy of corticosteroids is not 100%, a limited number of patients will continue to have breakthrough reactions. 8,9) Desensitization has long been used for refractory allergic reactions to common allergens such as bee venom or penicillin. It is defined as the graduated exposure of an allergen to a patient, in order to create a temporary state of tolerance to that agent.…”
Section: )mentioning
confidence: 99%